Some physical properties of SiO2 laser induced plasma - Abdulameer, Mohammed R. (Iraqi Journal of Science, 2022)
In this work; Silicon dioxide (SiO2) plasma plume was prepared by laser induced plasma (LIP). The electron number density, plasma frequency and Debye length were calculated by reading the data of I-V curve of Langmuir probe which was used as a diagnostic method of measuring plasma properties. Pulsed Nd:YAG laser was used for measuring the electron number density of SiO2 plasma plume under vacuum environment with varying both vacuum pressure and axial distance from the target surface. Some physical properties of the plasma generated such as electron density, plasma frequency and Debye length have been measured experimentally and the effects of vacuum pressure and Langmuir probe distance from the target were studied on those variables. An inverse relationships between electron density, Debye length and plasma frequency with axial distance from the target were observed as well direct proportionality between both plasma density and plasma frequency with vacuum pressure while the exception is true in case of Debye length which is proportional inversely with vacuum pressure.